Current Overview of Environmental Disinfection and Decolonization of C. auris: A Systematic Review from 2020 to 2025 - María Guadalupe Frías-De-León; Paola Betancourt-Cisneros; Erick Martínez-Herrera; Paola Berenice Zarate-Segura; Carlos Alberto Castro-Fuentes; Eduardo García-Salazar (Tropical Medicine and Infectious Disease)
Candida auris possesses distinctive features that facilitate its persistence and transmission in healthcare settings, causing outbreaks of infection that are difficult to treat. So, emphasis has been placed on implementing measures for controlling, eliminating, and preventing fungal transmission, such as environmental disinfection and patient decolonization. This review aimed to understand and analyze the agents for environmental disinfection and patient decolonization reported in the last 5 years. The PubMed database was reviewed, using the terms “Candida auris”, “disinfection”, and “decolonization”. Only original papers, published between 2020–2025, in English or Spanish, that included relevant information on the topic, were selected. After the selection process, 52 articles were chosen to analyze the agents for environmental disinfection and decolonization of C. auris. Natural and synthetic disinfectants and ultraviolet radiation were reported for the environmental disinfection, with variable efficacy, depending on factors such as concentration and exposure time. Natural and synthetic antiseptics were also reported for decolonization, with varying efficacy. For example, 2% chlorhexidine shows a 0.5 log reduction, while at concentrations >10% it is >4 log. However, most have only been tested in animal models. Based on the review, Far-UV-C radiation (222 nm) is safe and appropriate to mitigate (up to 1 log reduction) the spread of C. auris in the hospital setting. However, it is important to consider that the cost and limited availability of the device present a barrier to its implementation. Patient decolonization is still challenging nowadays due to the absence of agents with proven high efficacy in humans.